Imaging of Anaplastic Thyroid Carcinoma - Ahmed, S.; Ghazarian, M.P.; Cabanillas, M.E.; Zafereo, M.E.; Williams, M.D.; Vu, T.; Schomer, D.F.; Debnam, J.M. (American Journal of Neuroradiology, 2018)
SUMMARY: Anaplastic thyroid carcinoma is fatal if unresectable. However, improved survival has been reported after gross total resection and multimodality therapy. In this report, we describe the contrast-enhanced high-resolution CT characteristics of anaplastic thyroid carcinoma in 57 patients. Anaplastic thyroid carcinoma presented as a large neck mass with necrosis in 82% of cases. The tumors demonstrated common extrathyroidal extension (91%). Sixty-two percent of tumors demonstrated calcification. Visceral space invasion involved the esophagus (62%), trachea (57%), and larynx (29%). Carotid artery encasement was present in 42%, and 43% involved the internal jugular vein. Sixty-three percent had lateral compartment lymphadenopathy; 58% of these nodes were necrotic, and 11% were cystic. No metastatic nodes had calcification. Central compartment lymphadenopathy was seen in 56% of cases, and lateral retropharyngeal lymphadenopathy was detected in 12%. Knowledge of these imaging features aids in guiding the approach to the initial tissue diagnosis with either fine-needle aspiration or core biopsy, assessing the feasibility of surgical resection, and determining prognosis.ATCanaplastic thyroid carcinomaCECTcontrast-enhanced CTDTCdifferentiated thyroid cancer